Psychometric validation of the modified Chinese version of the personalized psychological flexibility index in patients with cancer - Wanting Xia; Mengyao Yan; Weilian Jiang; Meijun Ou; Chanjuan Xie; Xiangyu Liu; Xianghua Xu (Elsevier, 2023)
Objective: The aim of this study was to perform across-cultural adaptation of the English version of the personalized psychological flexibility index (PPFI) into Chinese, and to evaluate its psychometric properties in patients with cancer. Methods: This study was conducted in two phases. In phase 1, we followed Beaton's guidelines for cross-cultural adaptation of PPFI. In phase 2, we conducted a cross-sectional study to assess the validity and reliability of the PPFI among a total of 455 patients with cancer in Hunan Province of China. Item analysis was used to evaluate and screen items, while content validity, construct validity, convergent validity, and concurrent validity were used to evaluate the validity. Reliability was assessed using Cronbach's ɑ coefficient, retest reliability, and composite reliability. Results: The item-level content validity index of the modified Chinese version of PPFI (PPFI-C) ranged from 0.89 to 1.00, the scale-level CVI/universal agreement was 0.87, and the S-CVI/average was 0.99. Exploratory factor analysis identified a 14-item, three-factor structure of PPFI (item 11 deleted). Confirmatory factor analysis showed χ2/df ​= ​2.42, RMSEA ​= ​0.07, GFI ​= ​0.92, NFI ​= ​0.91, TLI ​= ​0.93, CFI ​= ​0.95, and IFI ​= ​0.95. PPFI-C demonstrated positive correlations with the 8-item Commitment Action Questionnaire, and negative correlations with Acceptance and Action Questionnaire-II, Hospital Anxiety and Depression Scale, and Short Form Quality Life Scale. The Cronbach's ɑ coefficient of modified PPFI-C stood at 0.84. Conclusions: The results suggest that the 14-item PPFI-C is a reliable and valid tool for measuring PF in Chinese patients with cancer. However, additional studies are needed to validate the psychometric properties of PPFI-C in other populations.